Single-cell kinetics of a repressilator when implemented in a single-copy plasmid1. Issue 7 (16th July 2015) - Oliveira, Samuel M. D.; Chandraseelan, Jerome G.; Häkkinen, Antti; Goncalves, Nadia S. M.; Yli-Harja, Olli; Startceva, Sofia; Ribeiro, Andre S.
<x xml:space="preserve">Abstract</x> We constructed a single-copy repressilator (SCR) by implementing the original repressilator circuit on a single-copy F-plasmid.